Marcados, de Claudia Andujar: do documento visual à imagem poética - Pereira, Vera Lúcia (2015)
This research deals with the photographic series titled Marked held by Swiss- Brazilian artist Claudia Andujar in the 1980s, portrays a group of Yanomami ethnic Indians in the period in which they lived the consequences of increasing contact with white society. Along with other works of Claudia Andujar, the Marked of images point to a singular creation process, which migrates from documentation to poetic dimension, allowing for reflection about the multiple relationships between aesthetics and politics, hence between art and life, including otherness processes present in the image building - key issues for theory and contemporary art history.